All Days 2008
DOI: 10.4043/19310-ms
|View full text |Cite
|
Sign up to set email alerts
|

Resource Assessment of Methane Hydrate in the Eastern Nankai Trough, Japan

Abstract: Resource assessment of methane hydrate (MH) in the eastern Nankai Trough was conducted through probabilistic approach using 2D/3D seismic data and drilling survey data from METI exploratory test wells " Tokai-oki to Kumano-nada??. We have extracted more than 10 prospective " MH concentrated zones?? characterized by high resistivity in well log, strong seismic reflectors, seismic high velocity, and turbidite deposit delineated by sedimentary facies analysis. The amount of methane gas contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 0 publications
0
56
0
2
Order By: Relevance
“…Thrust and growth faults, as well as bottom-simulating reflectors (BSRs) suggestive of the presence of hydrate, have been extensively investigated since 1971 with seismic surveys, coring, and logging Takahashi and Tsuji, 2005;Tsuji et al, 2004;Uchida et al, 2004;Waseda and Uchida, 2004a,b). The total amount of gas in place in the eastern Nankai Trough is estimated to be 1.1 trillion (10 12 ) cubic meters (Fujii et al, 2008). Isotope analyses suggest the methane gas in shallow sections of the Nankai Trough at the coring site for this study is mostly microbial, with only a slight increase of higher hydrocarbon concentrations with depth .…”
Section: Introductionmentioning
confidence: 86%
“…Thrust and growth faults, as well as bottom-simulating reflectors (BSRs) suggestive of the presence of hydrate, have been extensively investigated since 1971 with seismic surveys, coring, and logging Takahashi and Tsuji, 2005;Tsuji et al, 2004;Uchida et al, 2004;Waseda and Uchida, 2004a,b). The total amount of gas in place in the eastern Nankai Trough is estimated to be 1.1 trillion (10 12 ) cubic meters (Fujii et al, 2008). Isotope analyses suggest the methane gas in shallow sections of the Nankai Trough at the coring site for this study is mostly microbial, with only a slight increase of higher hydrocarbon concentrations with depth .…”
Section: Introductionmentioning
confidence: 86%
“…The pressure-temperature conditions that are necessary (but not sufficient) for gas hydrate formation (see Sloan and Koh, 2008) limit the occurrence of gas hydrates to arctic sediments (typically where the geothermal gradient is impacted by permafrost), to sediments within deep lakes and seas, and to shallow oceanic sediments on outer continental shelves and slopes where water depths exceed approximately 500 m. Gas hydrate occurs in a variety of forms and a range of geologic settings. In the marine environment, gas hydrate has been documented to occur as disseminated grains filling pores within sands (Riedel et al, 2006;Fujii et al, 2008) and muds (Paull et al, 1996;Yang et al, 2008), as well as complex networks of fracture fills, veins, and nodules primarily in fine-grained sediments Collett et al, 2008a;Park, 2008;Hadley et al, 2008). In contrast, permafrost-associated gas hydrates have commonly been reported to be primarily restricted to pore-filling morphologies within sandy sediments (Dallimore and Collett, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A number of new quan ta ve es mates of in-place methane hydrate volumes (Klauda and Sandler, 2005;Frye, 2008;Wood and Jung, 2008;Bureau of Ocean Energy Management, 2012) and, for the fi rst me, technical recoverable Fujii et al, 2008) assessments, have been undertaken using petroleum systems concepts developed for conven onal oil and natural gas explora on. For example, in an assessment of methane hydrate resources on the North Slope of Alaska, Colle et al (2008) indicated that there are about 2.42 trillion cubic meters (~85.4 trillion cubic feet) of technically recoverable methane resources within concentrated, sand-dominated, methane hydrate accumula ons in northern Alaska.…”
Section: Methane Hydrate Assessmentsmentioning
confidence: 99%
“…Furthermore, the MMS assessment indicated that reservoir-quality sands may be more common in the shallow sediments of the methane hydrate stability zone than previously thought. Fujii et al (2008) es mated a volume of about 1.1 trillion cubic meters (about 40 trillion cubic feet) of gas exists within the hydrates of the eastern Nankai Trough, with about half concentrated in sand reservoirs.…”
Section: High Methane Hydrate Concentra Ons Inmentioning
confidence: 99%